Tunable ionic and electronic conduction of lithium nitride via phosphorus and arsenic substitution : a first-principles study - Wu, Shunnian (2011)
We investigated the electronic structure and transport properties of phosphorus- and arsenic-substituted Li3N using first-principles methods. It is found that both P and As partial substitution reduce Li vacancy formation energy, without appreciable alteration of energy band gap, indicating an improvement in ionic conduction. But a full substitution of P and As results in variation of crystal structure from the space group P6/mmm to P63/mmc, and the energy band gaps of Li3P and Li3As are reduced to 0.72 and 0.65 eV, respectively, in comparison with 1.14 eV of Li3N. A full substitution also brings about an increase of Li vacancy formation energies, suggesting degradation in ionic conduction. Our calculations suggest that it would be viable to achieve balanced electronic and ionic conduction of Li3N by controlled P and As partial substitution.